2014
DOI: 10.1007/s12639-014-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of liver fluke infections in slaughtered animals in Lorestan, Iran

Abstract: Fasciola spp. and Dicrocoelium dendriticum as liver flukes, contaminate ruminants and other mammalian extensively and cause major diseases of livestock that create considerable economic losses. This retrospective study has been done to evaluate contamination rate of slaughtered animals with fasciolosis and dicrocoeliosis at Lorestan abattoirs. In this survey, prevalence rate of fasciolosis and dicrocoeliosis in slaughtered animals in a 3-year period (2010-2013) has been analyzed. A total of 356,605 livestock i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…The prevalence of liver fluke infections recorded in the present study was generally lower than those reported from other regions of Iran including Guilan (Daryani et al 2006), Mazandaran (Moghaddam et al 2004), Khouzestan (Sahba et al 1972), Lorestan (Ezatpour et al 2014), Ardabil (Saffarbani 1999), Fars (Ansari-Lari and Moazzeni 2006), Shahr-e Kord (Manouchehehri Naini and Bagheri 2000) and Tehran Provinces (Khanjari et al 2012).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The prevalence of liver fluke infections recorded in the present study was generally lower than those reported from other regions of Iran including Guilan (Daryani et al 2006), Mazandaran (Moghaddam et al 2004), Khouzestan (Sahba et al 1972), Lorestan (Ezatpour et al 2014), Ardabil (Saffarbani 1999), Fars (Ansari-Lari and Moazzeni 2006), Shahr-e Kord (Manouchehehri Naini and Bagheri 2000) and Tehran Provinces (Khanjari et al 2012).…”
Section: Discussioncontrasting
confidence: 61%
“…Based on the literature, there are numerous reports of fasciolosis and dicrocoeliosis from different countries in Asia such as Iraq, Pakistan, Turkey, Saudi Arabia, Tunisia, Bangladesh, India, China, Japan, Korea and also many parts of Iran (Ezatpour et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of dicrocoeliosis in sheep and goats varied from 3.63-20.0 and 2.6-5.0 percent respectively ( Khajuria et al, 2013;Khanjari et al, 2014;Godara et al, 2014;Ezatpour et al, 2015;Tan et al, 2017). Nevertheless, there were reports of 32 percent prevalence in goats from India (Lone et al, 2012).…”
Section: Dicrocoelium Sppmentioning
confidence: 99%
“…Khoramian et al (2014) found a prevalence of 3.28 % in central Iran and calculated a considerable economic loss. Ezatpour et al (2014) studied the prevalence of liver fluke in the abattoirs of Lorestan in Iran. They found a prevalence of 7.1 % overall in sheep and goats, with seasonal variation, whereby most condemnations were found in spring and autumn.…”
Section: Zoonotic Diseasementioning
confidence: 99%
“…Among the diseases that are considered relevant in this context, several zoonotic diseases as well as epidemic, often notifiable, diseases can be mentioned (EFSA 2011, EFSA 2012, EFSA 2013a, EFSA 2013b. Apart from that, there are a number of diseases that are neither epidemic nor zoonotic, but highly relevant for animal husbandry or on-farm health and welfare (MacGillivray et al, 2013, Ezatpour et al, 2014.…”
Section: Introductionmentioning
confidence: 99%